Arthritis care: comparison of physicians' and patients' views. - Lambert BL; Butin DN; Moran D; Zhao SZ; Carr BC; Chen C; Kizis FJ (Seminars in Arthritis & Rheumatism, 2000)
OBJECTIVES: To understand the expressed needs of physicians and their patients with respect to arthritis care, identify areas of agreement and disagreement in doctor and patient views of arthritis care, and to determine the types of educational programs needed. METHODS: Focus group interviews were conducted with 14 physicians of varied specialties and 12 patients with arthritis from Oxford Health Plans. Interviews were audiotaped and transcribed. Analyses were performed by using text processing programs from the Unix computer operating system. Common themes were identified and summarized. RESULTS: Physicians and patients agreed that pain and loss of functioning were the most important problems patients with arthritis faced and that arthritis was incurable. Both agreed that doctors need more time to discuss individual concerns with their patients. More information about diet and exercise and strategies for reducing social isolation were needed. Doctors and patients disagreed about the value of nutritional supplements, joint replacement, and referrals to specialists. Disagreement also existed regarding the belief that pain was an inevitable part of the aging process, and with respect to the use of drug and surgical therapy. CONCLUSIONS: Areas of agreement and disagreement were discussed. Collaboration and negotiation were identified as constructive responses to conflicts between physicians and patients. Patients need to be taught self-care strategies to minimize the impact of arthritis on their daily lives. The specific continuing education needs of physicians involved training in exercise, nutrition, occupational and physical therapy, prescriptions, and alternative medicine. Copyright © 2000 by W.B. Saunders Company